Stunting in Children Aged 0-5 Years: A Literature Review on Prevention and Control Strategies - Meilin Anggreyni; Ince Rahmi; Rizka Rizka; Sudirman Sudirman; Ahmad Yani; Finta Amalinda (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Stunting is a significant public health issue affecting children under five years old, leading to long-term consequences on growth and development. The method used in this study is Systematic Literature Review (SLR). Research conducted systematically by following the rules with the flow of literature review to avoid subjective misunderstandings from researchers. The data used in the study are sourced from national and international scientific publication databases such as PubMed, Google Scholar and Science Direct. The search keywords for the article are arranged based on the PICOS Framework, the keywords are